Characterizing and Predicting Which Bugs Get Reopened - Zimmermann, Tom; Nagappan, Nachi; Guo, Philip J.; Murphy, Brendan (Proceedings of the 34th International Conference on Software Engineering (ICSE 2012 SEIP Track), 2012)
Fixing bugs is an important part of the software development process. An underlying aspect is the effectiveness of fixes: if a fair number of fixed bugs are reopened, it could indicate instability in the software system. To the best of our knowledge there has been on little prior work on understanding the dynamics of bug reopens. Towards that end, in this paper, we characterize when bug reports are reopened by using the Microsoft Windows operating system project as an empirical case study. Our analysis is based on a mixed-methods approach. First, we categorize the primary reasons for reopens based on a survey of 358 Microsoft employees. We then reinforce these results with a large-scale quantitative study of Windows bug reports, focusing on factors related to bug report edits and relationships between people involved in handling the bug. Finally, we build statistical models to describe the impact of various metrics on reopening bugs ranging from the reputation of the opener to how the bug was found.